Alignment of Learning Outcome Assessment Approaches at Polytechnic Colleges - Temesgen Tadele Asratie; Prem J Heeralal (International Journal of Educational Innovation and Research, 2026)
In the learning process assessment approaches have decisive roles in addressing competencies. This study aimed to investigate the alignment of learning outcome assessment approaches at polytechnic colleges in Addis Ababa, Ethiopia. A quantitative research design was employed. Out of six polytechnic colleges three were selected by using random sampling. Then, questionnaires were used to collect data from 202 polytechnic college trainers and 358 trainees. Moreover, 3 college deans, 3 department heads, 6 trainers, and 6 trainees were involved in structured interview. The study employed both descriptive and inferential statistics. The result of the study depicted that there was a weak alignment among learning outcome assessment approaches. Moreover, assessment practice faced challenges due to weak connections among training components, including learning objectives and assessment approaches. There was a statistically significant mean difference between trainers and trainees view towards alignment among learning outcome assessment approaches. Finally, the study figured out that the extent of aligning learning outcome assessment approaches at polytechnic college was suboptimal. Therefore, professional development program should be given to improve the alignment practice among learning objectives, assessment approaches and the assessment activities.